Catch per unit effort estimation and factors influencing it from recreational angling of sockeye salmon (Oncorhynchus nerka) and management implications for Lake Toya, Japan. Issue 4 (December 2015) - Sweke, Emmanuel A.; Su, Yu; Baba, Shinya; Denboh, Takashi; Ueda, Hiroshi; Sakurai, Yasunori; Matsuishi, Takashi
Abstract: The present study examined the factors influencing catch per unit effort (CPUE) and standardized the CPUE of sockeye salmon ( Oncorhynchus nerka ) from offshore angling in Lake Toya, northern Japan. A generalized linear model (GLM), based on a negative binomial error distribution, was used to standardize the catch‐and‐effort data collected from anglers, using questionnaires and interview surveys during the fishing season (June) in 1998, 1999 and 2001–2012. Year, week, fishing area, number of fishing rods, fishing duration and Year × Week were the factors that significantly ( P < 0.05) influenced CPUE. Anglers' fishing experience had no significant effect ( P = 0.06) on CPUE. Limiting fishing duration, number of anglers and fishing rods may reduce fishing pressure and ensure sustainable management of the fishery. The results of the present study on standardized CPUE can also be useful in fine‐tuning age‐based models, such as Virtual Population Analysis (VPA–ADAPT), for the fish species in the lake, studies that are currently lacking. Regular and interdisciplinary studies that include biophysical factors are required to provide more understanding of the variations in the abundance of the fish species in the lake and in the ecosystem at large.